The Influence of Work Discipline on Employee Performance at Karya Bangsa - Tyagita Dianingtyas Sudibyo (Yayasan Putra Adi Dharma, 2024)
This study aims to analyze the influence of work discipline on employee performance at Karya Bangsa. Work discipline is an important factor that can affect the level of employee performance in an organization. The research method used is quantitative, with data collected through questionnaires distributed to 80 employees of Karya Bangsa. Data analysis was conducted using simple linear regression analysis to determine the extent of the influence of work discipline on employee performance. The results of the study show that work discipline has a positive and significant impact on employee performance. The correlation coefficient indicates a strong relationship between the two variables, with an R Square value of 65%, meaning that 65% of the variability in employee performance can be explained by work discipline. Based on these findings, it is recommended that Karya Bangsa continue to improve employee work discipline through various effective training and supervision programs.